Ventricular arrhythmia as an initial sign in acute Kawasaki disease: A case report. Issue 18 (May 2018) - Hu, Fan; Shi, Xiaoqing; Li, Yifei; Hua, Yimin; Zhou, Kaiyu
Abstract: Rationale: Coronary artery lesion is the most prominent cardiac manifestation in Kawasaki disease. However, few cases of life-threatening cardiac arrhythmia were reported in the acute phase of Kawasaki disease. Patient concerns: A 1-year-old girl presented in the hospital with ventricular premature beats and ventricular tachycardia after 2 days of fever. Diagnosis: On the fifth day of fever, the diagnosis of Kawasaki disease was achieved. Interventions: Immunoglobulin was administered. Outcome: The temperature became normal and ventricular arrhythmia disappeared. Lessons: This case suggests that Kawasaki disease has various clinical manifestations besides typical features, and it can cause life-threatening cardiac arrhythmia in the acute phase with normal coronary artery and normal cardiac function.